2016
DOI: 10.4172/2471-9870.1000115
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of CogCardio: Cognitive Rehabilitation in Cardiac Patients

Abstract: Cognitive deficits pose serious challenges for cardiac patients. Various paper-pencil and computerized intervention paradigms have been developed and explored in pilot and feasibility studies. However, they are limited in scope and applicability. Therefore, there is a growing need to develop and standardize cognitive retraining activities that address all affected domains in the different cardiac conditions and ensure functional independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, it is important to consider that experiences in the period prior to the onset of the disease influence the beliefs of patients and their perception of treatment [ 6 , 36 ]. Therefore, it is important to understand the characteristics related to the health and pathology in question, considering the collective and individual experiences of the patients [ 11 , 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to consider that experiences in the period prior to the onset of the disease influence the beliefs of patients and their perception of treatment [ 6 , 36 ]. Therefore, it is important to understand the characteristics related to the health and pathology in question, considering the collective and individual experiences of the patients [ 11 , 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cardiovascular diseases have shown that HF is the main cause of hospitalisations in people over 65 years of age in Europe [ 6 , 7 ]. In both Europe and the United States, between 5.0% and 9.0% of people over 65 years of age suffer from HF.…”
Section: Introductionmentioning
confidence: 99%